Cover Picture: Direct Atomic‐Level Imaging of Zeolites: Oxygen, Sodium in Na‐LTA and Iron in Fe‐MFI (Angew. Chem. Int. Ed. 44/2020). Issue 44 (31st August 2020) - Mayoral, Alvaro; Zhang, Qing; Zhou, Yi; Chen, Pengyu; Ma, Yanhang; Monji, Taro; Losch, Pit; Schmidt, Wolfgang; Schüth, Ferdi; Hirao, Hajime; Yu, Jihong; Terasaki, Osamu
Abstract : The location and identification of all framework atoms in zeolites, including oxygen bridges, extra‐framework cations, and isomorphous substitution of Si, are reported by A. Mayoral, O. Terasaki et al. in their Research Article on page 19510 . The structures of two important zeolites, Na‐LTA and Fe‐MFI, were studied by using two complementary electron detectors in an aberration‐corrected electron microscope. It is the first direct observation of single transition metal atoms (Fe), which were found to be unevenly substituting the Si at the atomic level in the MFI framework.